Uji Antifertilitas Kombinasi Fraksi Kloroform Biji Pepaya (Carica papaya Linn.) dengan Fraksi Metanol Biji Saga (Abrus precatorius Linn.) terhadap Spermatogenesis Tikus Jantan Galur Wistar (Antifertility Study from Combination of Chloroform Fractions o - Zainah Rajab; Siti Muslichah; Fifteen Aprila Fajrin (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Chloroform fraction of Carica papaya seed (FKCP) and methanol fraction of Abrus precatorius seed (FMAB) have antifertility activity. This study aims to determine the antifertility activity combination of FKCP and FMAB in spermatogenesis and its reversibility on wistar male rats. This research used 40 wistar male rats that were divided into 5 groups, eight animals each group. Grup P0 (control) was administered by CMC Na 1%, group P1 was administered by combination of FKCP dose of 100 mg/kg BW and FMAB dose of 75 mg/kg BW, group P2 was administered by combination of FKCP dose of 100 mg/kg BW and FMAB dose of 50 mg/kg BW, group P3 was administered by combination of FKCP dose of 50 mg/kg BW and FMAB dose of 75 mg/kg BW, grup P4 was administered by combination of FKCP dose of 50 mg/kg BW and FMAB dose of 50 mg/kg BW for 28 days. Reversibility of spermatogenesis was observed in all group after 28 days of withdrawal of treatment. The results showed degenerative changes in the seminiferous tubules of rats given FKCP and FMAB. Conclusion of this research is the combination of these fractions reduced spermatogenesis, but it was reversible. Keywords: antifertility, saga seed, papaya seed, spermatogenesis, reversibility.